PENINGKATAN KAPASITAS PENGURUS BUMDESA MELALUI PELATIHAN DI KABUPATEN CIANJUR: Building Capacity Of Village Owned Enterprises Administrators Through Training In Cianjur Regency - Yolanda, Riska (Prospect Publishing, 2025)
Village-Owned Enterprises are the locomotive of development in the village motivated by the initiative of the government and the village community. BUMDesa is expected to be able to become a driving force for economic activities in the village so that it can improve the welfare of the community. Ideally, BUMDes have a significant influence on economic growth but there are still obstacles faced, one of which is the problem of human resources. The training is one of the capacity building programs for BUMDesa administrators carried out by the Jakarta Center for Training and Empowerment of Village, Disadvantaged Regions and Transmigration. The training activity was carried out for 4 days which was attended by ten villages in Cianjur Regency. It is hoped that this training will increase the knowledge and competence of BUMDesa administrators. The type of research used is a descriptive qualitative method with an evaluative approach, namely the evaluation of the implementation of the training that has been carried out. The results of the study show that the task of the facilitator in the training, namely Non-Governmental Mobilizers, has been running well. The knowledge of the trainees has increased, as can be seen from the comparison of pre-test and post-test scores during the training. From the average pre-test score of 51.97, it increased during the post test to 71.40. The trainees felt the impact of increasing their understanding and skills during the training. This will affect their performance in managing BUMDesa so that BUMDesa businesses can develop